2018
DOI: 10.3390/genes9060287
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Fragile X Syndrome in a Twin Pregnancy Complicated by a Complete Retraction

Abstract: Fragile X syndrome (FXS) is usually associated with a CGG repeat expansion >200 repeats within the FMR1 gene, known as a full mutation (FM). FM alleles produce abnormal methylation of the FMR1 promoter with reduction or silencing of FMR1 gene expression. Furthermore, premutation (PM: 55–199 CGGs) and full mutation alleles usually expand in size when maternally transmitted to progeny. This study describes a PM allele carried by the mother decreasing to a normal sized allele in a male from a dichorionic diamniot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Contracted alleles detected in FXS families in a non-mosaic state have already been reported by us, in an unaffected boy who inherited an allele of 43 CGGs derived from a large PM (around 190 CGGs) carried by his mother [21]. Similar reverted and non-mosaic alleles have been described in FXS families both in unaffected females [19,22] and in unaffected males [23,24]. Contracted alleles in the range of normality have also been detected along with expanded ones in FXS mosaic males, such as in the four affected boys reported by Maia et al [25], who inherited the normal allele by their FM or PM mother, or as in a monozygous male twin, who derived the normal allele from his PM mother [26].…”
Section: Discussionsupporting
confidence: 80%
“…Contracted alleles detected in FXS families in a non-mosaic state have already been reported by us, in an unaffected boy who inherited an allele of 43 CGGs derived from a large PM (around 190 CGGs) carried by his mother [21]. Similar reverted and non-mosaic alleles have been described in FXS families both in unaffected females [19,22] and in unaffected males [23,24]. Contracted alleles in the range of normality have also been detected along with expanded ones in FXS mosaic males, such as in the four affected boys reported by Maia et al [25], who inherited the normal allele by their FM or PM mother, or as in a monozygous male twin, who derived the normal allele from his PM mother [26].…”
Section: Discussionsupporting
confidence: 80%
“…Prenatal testing for FXS typically involves foetal sex determination by karyotype and or Flurorescent In Situ Hybridization (FISH), followed by sizing of the FMR1 allele either through Southern blot and CGG PCR sizing or through Triplet Repeat Primed PCR and linkage techniques [10]. Presence of mosaicism due to somatic retraction is of particular concern for prenatal testing, where FM alleles are present in a small proportion of cells due to tissue and/or CGG size mosaicism [11,12]. The most extreme example of such retraction has recently been observed in a twin pregnancy, where a couple chose not to terminate, finding a fully retracted seemingly functional normal size allele postnatally in absence of a FM in the male twin [12].…”
Section: Introductionmentioning
confidence: 99%
“…Presence of mosaicism due to somatic retraction is of particular concern for prenatal testing, where FM alleles are present in a small proportion of cells due to tissue and/or CGG size mosaicism [11,12]. The most extreme example of such retraction has recently been observed in a twin pregnancy, where a couple chose not to terminate, finding a fully retracted seemingly functional normal size allele postnatally in absence of a FM in the male twin [12].…”
Section: Introductionmentioning
confidence: 99%
“…Nolin et al reported 28 contractions events (on 1040 transmissions), with an average loss of five repeats and 10 repeats, for paternal and maternal transmissions, respectively, and no association with AGG structures. Occasional cases of contraction of FMR1 PM or FM to a normal‐sized allele have been documented . In all these cases, the normal CGG repeat was different in size between the offspring and his/her mother.…”
Section: Discussionmentioning
confidence: 99%
“…While CGG repeat instability almost constantly expresses as an expansion, significant contraction events have occasionally been reported. Most of them manifest through reduction in size within the PM range, while very few cases of reversion from FM/large PM to a normal allele have been reported . These rare events have an important implication for the prenatal diagnosis (PND) of FXS: They indeed prohibit using polymorphic marker haplotyping as the only tool to predict the fetus status, even in women with large PM (greater than 90 CGGs) or FM.…”
Section: Introductionmentioning
confidence: 99%